MUSTAHIK EMPOWERMENT PROGRAM AND ITS IMPACT ON MUSTAHIK WELFARE: THE ECONOMIC IMPACT OF ZAKAT-BASED MUSTAHIK PROGRAMS IN INDONESIA - Laily, Alfauzia Noer Rochmatul; Noor, Iswan; Ekawaty, Marlina (Journal of Indonesian Applied Economics, 2025)
Purpose This study aims to evaluate the effectiveness of the Rumah Gemilang Indonesia (RGI) empowerment program in improving the material and spiritual welfare of mustahik, aligning with Islamic principles of holistic well-being. Design/methodology/approach A mixed methods approach was employed, integrating qualitative in-depth interviews with program managers and participants and a quantitative survey of 200 respondents. The CIBEST model was used to measure welfare dimensions, while data reliability was ensured through Pearson-Correlation and Cronbach's Alpha tests. Findings The study reveals a significant improvement in participants' welfare, with average incomes rising from IDR 615,821 to IDR 2,829,000, exceeding the poverty line. Spiritual well-being also improved, indicated by consistent worship practices and stronger religious values. CIBEST analysis showed an increase in mustahik in the prosperous quadrant and a reduction in absolute poverty. Key program strengths included holistic training, family support, and post-program assistance. Research limitations/implications The findings are limited to the specific context of the RGI program and may not fully generalize to other empowerment models. The study underscores the importance of integrating material and spiritual dimensions in zakat-based empowerment initiatives. Originality/value This research fills a gap in evaluating zakat-based empowerment programs through a holistic lens, combining material, spiritual, and social impacts. It contributes to the literature on Islamic economics by demonstrating the practical application of the CIBEST model in poverty alleviation and welfare enhancement.